Efeito de 2-aril(heteroaril)-4,5-diidro-1h-imidazóis sobre a atividade da enzima monoamina oxidase in vitro - Anna, Gabriela da Silva Sant (2008)
Monoamine oxidase (MAO) is a flavin adenine dinucleotide (FAD)-containing enzyme attached to the mitochondrial outer membrane of neurons, glia, and other cells. Its roles include regulation of the levels of biogenic and xenobiotic amines in the brain and peripheral tissues by catalyzing their oxidative deamination. On the basis of their substrate and inhibitor specificities, two isoforms of MAO have been described (A and B). Due to their role in the metabolism of catecholamines neurotransmitters, MAO-A and MAO-B have long been of pharmacological interest. Accordingly, and reversible and irreversible inhibitors of MAO-A and MAO-B have been used in the clinics to treat neurological disorders including depression and Parkinson´s disease. Since the demonstration that I2- imidazoline sites are associated with mitochondrial membranes 15 years ago, several studies have provided evidence that these sites represent regions on MAOs. In line with this view, it has been demonstrated that imidazoline derivatives inhibit MAO activity. This effect has been attributed to a high affinity I2 binding site on MAO-B (I2B) and to a similar lower affinity site on MAO-A (I2A). This study investigated the effect of 4,5-dihydro-1H-imidazole-2-substituted compounds on MAO activity in vitro by spectrophotometric and fluorimetric methods using kynuramine as substrate. Among the compounds that inhibited MAO-A (3c-e, 3j), compound 3d was 73-fold more selective towards MAO-A than MAO-B. Among the compounds that selectively inhibited MAO-B (3g-I, 3k, 3o), imidazoline 3g was shown to be potent with Ki value of 5,3 μM. Some of compounds that selectively bind to I2-sites, such as 3l (benazoline), 3n (2-BFI), and 3p (BU224) showed good inhibitory activity especially against MAO-B. Imidazolines inhibited MAO-A and MAO-B activities in liver with less selectively than in rat brain. The compounds 3d and 3g reversibly inhibited MAO, and kinetics studies showed that compound 3d and 3g inhibited MAO in a mixed manner (decreased Vmax and increased Km values). These results confirm that imidazolines inhibit MAO activity and suggest a relationship between I2 binding site and modulation of central MAO